2013
DOI: 10.1371/journal.pone.0058684
|View full text |Cite
|
Sign up to set email alerts
|

HPV and Genital Warts among Peruvian Men Who Have Sex with Men and Transgender People: Knowledge, Attitudes and Treatment Experiences

Abstract: BackgroundSeveral studies have assessed the epidemiology of HPV infection among MSM, but no qualitative studies have specifically assessed how HPV and genital warts (GW) affect South American men who have sex with men (MSM) and male-to-female transgendered women (TG). This study explored the knowledge, attitudes and experiences of Peruvian MSM and TG regarding HPV and GW.MethodsWe performed a qualitative study consisting of fifteen in-depth interviews and three focus groups carried out in Lima, Peru with diver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
0
6

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(30 citation statements)
references
References 37 publications
(41 reference statements)
1
23
0
6
Order By: Relevance
“…As with other studies on knowledge of HPV and anal cancer, 16,17 participants in the present study were to a great extent uninformed and largely unaware of the link between HPV and anal cancer and the risk HPV and anal cancer presented to MSM. This is problematic for both clinicians and patients alike.…”
Section: Discussionmentioning
confidence: 54%
“…As with other studies on knowledge of HPV and anal cancer, 16,17 participants in the present study were to a great extent uninformed and largely unaware of the link between HPV and anal cancer and the risk HPV and anal cancer presented to MSM. This is problematic for both clinicians and patients alike.…”
Section: Discussionmentioning
confidence: 54%
“…Consistent with this, 77% of HIV negative MSM and TW have condom-less anal or oral sex [40]. EGW are traumatic for MSM, leading some to change from being the passive to the active partner, or to have sex in darkness [41]. Two-thirds of those with EGW would accept HPV vaccination for prophylaxis against HPV-attributable diseases [40].…”
Section: Peruvian Attitudes Towards Hpv Hpv-related Diseases and Hpmentioning
confidence: 78%
“…HPV prevalence in Peruvian men who have sex with men (MSM) is 77.1%, of which 47.3% are high risk HPV [41]. Peruvian transgender women (TW) may have an anogenital HPV prevalence of 95.6%, with a 47.8% HR HPV type prevalence [42].…”
Section: Peruvian Attitudes Towards Hpv Hpv-related Diseases and Hpmentioning
confidence: 99%
“…29 The univariate analysis findings that engaging in transactional sex and self-identifying as a transwoman were significantly associated with a lower risk of anogenital warts could be related to greater awareness of anogenital warts in these groups. 30 Also, the finding that having more than 10 episodes of anal intercourse in the previous 3 months, compared with 3 or fewer episodes, was significantly associated with a 60% decrease in risk of having anogenital warts might be explained by more frequent condom use. Nyitray et al, 17 for example, found that MSM who never used condoms for anal intercourse were 6 times more likely to have anal canal HPV compared with MSM who always used condoms; however, that study did not consider the presence of visible anogenital warts.…”
Section: Discussionmentioning
confidence: 99%